Effect of processing on biofunctionality of selected tropical fruit juices - Esquivel Rodríguez, Patricia (2022)
This review compiles the current state of knowledge on the effects of processing using thermal and nonthermal technologies and fermentation on selected compounds in potentially health-promoting tropical fruit juices, specifically those of pineapple, pitaya, guava, and papaya. The most relevant functional compounds in pineapple fruit are phenolic compounds, carotenoids, and vitamin C. Pitaya fruit functional properties are mainly defined by the presence of betalains, heat-labile molecules with high antioxidant potential. The guava fruit is very-well-known because of its high ascorbic acid contents and, depending on the genetic background, also lycopene and anthocyanins. Finally, the relevance of the papaya fruit relies mostly on high carotenoid contents and their role as precursors of vitamin A and as antioxidants. For every case, the pertinent functional constituents are summarized followed by a description of the effect of conventional and emerging processing strategies on their retention. Fermentation is also mentioned as an option to improve biofunctionality in certain cases.